OP0336 The effect of timing and duration of statin exposure on the risk of revision following total hip or knee arthroplasty: a population-based cohort study. (12th June 2018) - Cook, M.; Sorial, A.K.; Lunt, M.; Board, T.; O'Neill, T.
Abstract : Prevention of OA: Yes we can! Background: Total hip/knee replacement (THR/TKR) are safe and effective interventions for the treatment of osteoarthritis. However, around 2.5% of patients who undergo a THR/TKR in the UK require revision surgery within 5 years. Experimental studies have suggested that statins may have a beneficial effect on bone by promoting osteoblast formation and reducing osteoclastic bone resorption. Statins have been linked to improved strength of the bone-implant interface and may also attenuate the inflammatory response to particulate wear debris and subsequent periprosthetic osteolysis. Observational data suggest that postoperative exposure to statins may reduce the risk of revision arthroplasty. However, the influence of timing of statin exposure on revision risk has not previously been investigated. This may be significant since statins may affect biological processes occurring at different postoperative periods. Objectives: To determine whether the timing of statin exposure relative to the primary arthroplasty influences the risk of revision arthroplasty. Also to determine whether the duration of exposure is associated with the risk of revision arthroplasty. Methods: Subjects from the Clinical Practice Research Datalink, a population-based clinical database, who had THA/TKA from 1988–2016 were included. Cox regression models were used to determine the association between statin exposure and the risk of revision THA/TKA, i) at any time and ii) if first exposed 0–1, 1–5, or >5 years following THA/TKA. Cox regression was also used to determine the association between total duration of statin exposure (<1, 1–2, 2–3, 3–4, 4–5, >5 years) and revision risk. The Cox regression models were adjusted for the propensity score for statin exposure in each period, which was calculated using a logistic regression model including demographic factors, selected comorbidities and selected medication. Missing data for covariates were imputed using multiple imputation by chained equations with 10 iterations. Results: 1 51 305 participants were included. 57 003 (37.7%) were exposed to statins during follow up and 3500 (2.3%) had revision arthroplasty. In a propensity score adjusted model, exposure to statins was associated with a reduced risk of revision arthroplasty (HR (95% CI) 0.82 (0.75, 0.90)). Participants first exposed within 1 year and between 1 and 5 years following THA/TKA (vs unexposed) had a reduced risk of revision arthroplasty (HR (95% CI) 0.82 (0.74, 0.91) and 0.76 (0.65, 0.90), respectively), while first exposure >5 years following THA/TKA was not associated with revision risk. In relation to duration of statin therapy, participants exposed for more than 5 years in total (vs <1 year) had a reduced risk of revision (HR (95% CI) 0.74 (0.62, 0.88)). Conclusions: Statin therapy initiated up to 5 years following THA/TKA may reduce the risk of revision arthroplasty. The mechanisms by which statin therapy is linked with a reduced risk of revision surgery are not completely understood, though does not appear to be related solely to an effect on osseointegration of the primary prosthesis, which occurs primarily in the early (<1 year) postoperative period. Acknowledgements: The authors are grateful to the John Charnley Trust and the Three Wishes Foundation for supporting this research. Disclosure of Interest: None declared